Crescimento, desenvolvimento e nutrição de pinhão mansoadubado com lodo de esgoto e silicato de cálcio e magnésio - Fabiano Barbosa de Souza Prates (2010)
The objective of this study was to evaluate the growth, the development and the nutrition of physic nut in response to application of sewage sludge and calcium of silicate and magnesium in the soil. The experiment was conducted in the period from April 2008 to December 2009 in the area of the Institute of Agricultural Sciences of the UFMG, in Montes Claros - MG, latitude 16 ° 51'38 "S and longitude 44 ° 55'00" W in Haplic Cambisol. The treatments, in a factorial scheme 5 x 2, distributed in randomized block design with three replications, corresponded to 5 servings of dehydrated sewage sludge (0; 4.8; 9.6; 14.4 and 19.2 t ha -1) and 2 doses of silicate of calcium and magnesium (0 and 1 t ha-1). At the beginning of first flowering were collected soil samples at 0-20 and 20-40 cm deep and of the oldest leaf not senescent and of the youngest leaf fully expanded for analysis of macronutrients and heavy metals. Were determined in the 18th month of planting the stem diameter (DC), of the crown (DCO) and height of the plant (ALT). The application of silicate of calcium and magnesium in soil increased the pH, the contents of phosphorus, calcium and magnesium available, the availability of iron, nickel, zinc and manganese in the soil beyond the increase in magnesium content and reduction of contents of zinc and copper in leaves of physic nut, but did not influence the growth and development of physic nut. Sewage sludge, on the other hand, promoted increase of the contents of organic matter, nitrate, phosphorus, iron and copper and the reduction of lead content in soil, in the plant there were increasing of phosphorus, calcium, nitrogen, magnesium, zinc, iron, manganese and copper, which reflected in a greater increase in the DCO, with the increment of this residue until the dose of 11 t ha-1. There were no relevant interactions between the sewage sludge and silicate, and neither the effect of this last on growth and plant development, recommending only the application of sewage sludge in the cultivation of physic nut. The levels of heavy metals in soil and plant remained within the limits established by CONAMA Resolution No. 375, with the application of 11 t ha-1 of sewage sludge, recommended as the best dose for the fertilization of physic nut.